Brain Wave Changes during Cognitive Task Performance in Uncomplicated Diabetic Adults: An Exploratory Study - Sim, Sze Kiat; Madzlifah, Ahadon; Sohail, Mushtaq (International Islamic University Malaysia, 2022)
Introduction: Diabetes mellitus (DM) is a chronic disease associated with cognitive decline and dementia in the elderly population. This exploratory study analysed the brain wave changes during cognitive task performance in working adults with and without type 2 diabetes mellitus (T2DM). MATERIALS AND Methods: The Mini-Mental State Examination was used to screen subject’s cognitive function and quantitative electroencephalography was used to analyse subject’s brain waves at rest and whilst performing the serial seven test. Results: When performing the serial seven test, the diabetic group showed a higher absolute power of theta waves in the left frontal (Fp1, 16.22 ± 3.81 vs 3.75 ± 1.69; p = 0.022) and temporal regions (T3, 24.27 ± 3.69 vs 7.92 ± 2.17; p = 0.045), but lower absolute power of beta waves in both the frontal regions (Fp1, 27.35 ± 3.67 vs 41.14 ± 5.67; p = 0.029; Fp2, 23.01 ± 3.31 vs 39.05 ± 2.64; p = 0.041) and left temporal region (T3, 37.93 ± 4.64 vs 50.94 ± 3.56; p = 0.046) when compared to those of the control group. The diabetic group took longer to complete the task (127.9 ± 8.3 s vs 95.6 ± 5.9 s; p = 0.032) than the control group, despite no statistically significant difference in correct response rates. Diabetes duration was positively correlated with the theta/alpha ratio in the left frontal (Fp1, r = 0.525; p = 0.041) and temporal (T3, r = 0.618; p = 0.037) regions. Conclusions: T2DM may affect cognitive function in patients before clinical manifestation.